DNA tests in prolific sheep from eight countries provide evidence on origin of the Booroola (FecB) mutation - Davis, G.H.; Galloway, S.M.; Ross, I.K.; Gregan, S.M.; Ward, J.; Nimbkar, B.V.; Ghalsasi, P.M.; Nimbkar, C.; Gray, G.D.; Subandriyo, I.I.; Tiesnamurti, Bess; Matyniuk, E.; et al. (2002)
Recent discoveries that high prolificacy in sheep carrying the Booroola gene (FecB) is the result of a mutation in the BMPIB receptor and high prolificacy in Inverdale sheep (FecXI) is the result of a mutation in the BMP15 oocyte-derived growth factor gene have allowed direct marker tests to be developed for FecB and FecXI. These tests were carried out in seven strains of sheep (Javanese (Indonesia), Thoka (Iceland), Woodlands (New Zealand), Olkuska (Poland), Lacaune , Belclare (Ireland) and Cambridge (Ireland)) in which inheritance patterns have suggested the presence of major genes affecting prolificacy and in the prolific Garole sheep of India, which have been proposed as the ancestor of Australian Booroola Merinos. The FecB mutation was found in the Garole and Javanese sheep but not in Thoka, Woodlands, Olkuska, Lacaune, Belclare and Cambridge sheeNone of the sheep tested had the FecXI mutation. These findings present strong evidence to support historical records that the Booroola gene was introduced into Australian flocks from Garole (Bengal) sheep in the late 18th century. It is unknown whether Javanese Thin-tailed sheep acquired the Booroola gene directly from Garole sheep from India or via Merinos from Australia. The DNA mutation test for FecB will enable breeding plans to be developed that allow the most effective use of this gene in Garole and Javanese Thin-tailed sheep and their crosses.